Letter (copy) : Spain - Citrine, Walter, 1887-1983
023_0012_001 Secretary's PERSONAL. 20th May, 1937. Mr. E. Fimmen, International Transportworkers' Federation, VondeIstraat, 61, AMSTERDAM, W. HOLLAND. Dear Mr. Fimmen, SPAIN. Thank you for your letter of the 14th May, giving me further information which I am passing on to the right quarter. I should be glad to have any more instances which come to your notice. Yours sincerely, General Secretary. 292/946/23/13